Mednarodna, EU in primerjalnopravna raziskava dela na domu - Bagari, Sara (Delavci in delodajalci, 2020)
The paper deals with the regulation of home work at international, EU and comparative legal level. Although Slovenia has not yet ratified the ILO Home Work Convention no. 177, its standards can serve as a guide and inspiration in the interpretation and development of national legislation. In the acquis communautaire, homework is regulated by Framework agreement on telework. In addition to the latter, the paper presents other recent directives which the legislator must take into account when changing national regulation on home work. In the third part, the article answers the question how homework is regulated in some other EU member states.
Keywords: delo na daljavo; delo na domu; delovno pravo; Framework Agreement on Telework; home work; Home Work Convention No. 177; Konvencija o delu na domu št. 177; legal regulation; Okvirni sporazum o delu na daljavo; pravna ureditev; telework